Implementasi Sosialisasi Penulisan 3s pada Asuhan Keperawatan Gawat Darurat Pasien Hipertensi Emergency untuk Meningkatkan Profesional dalam Penulisan 3S di IGD RS Ar Rasyid Palembang Tahun 2025 - Saputra, Joko Hendra; Anggraini, Novita Ana (Green Publisher Indonesia, 2025)
Hypertensive emergency is a critical condition that requires prompt, accurate, and professionally documented nursing care through standardized nursing processes. One of the challenges in the Emergency Department of Ar Rasyid Hospital Palembang is the suboptimal implementation of 3S-based nursing documentation (SDKI, SLKI, and SIKI) for patients with hypertensive emergencies. This community service activity aimed to enhance nurses’ professionalism through the implementation of socialization on 3S nursing documentation in emergency nursing care. The methods included an initial survey, interviews, observations, and the administration of pre-test and post-test, followed by socialization sessions and simulation of 3S documentation. The participants consisted of head nurses, team leaders, and staff nurses in the emergency department. The evaluation results demonstrated a significant improvement in nurses’ knowledge and understanding after the intervention, as reflected by higher post-test scores compared to pre-test scores. Furthermore, the implementation of 3S documentation became more consistent in emergency nursing records, both manually and through electronic medical records. This activity confirms that socialization and simulation of 3S documentation are effective strategies to improve the quality and professionalism of emergency nursing care for hypertensive emergency patients in hospital emergency departments.